Predicting 30 m timing gate speed from a 5 Hz Global Positioning System (GPS) device - Waldron, M.; Worsfold, P.; Twist, C.; Lamb, K. (International Journal of Performance Analysis in Sport, 2011)
The measurement of over-ground human locomotion using global positioning systems (GPS) has many potential research applications, one of which is the assessment of linear sprint performance. Although recent studies have reported 5 Hz systems to underestimate speed determined by infra-red timing gates, which are commonly used to assess linear speed over brief 10 to 30 m intervals, the magnitude and direction of error are yet to be clarified. Therefore, the purpose of this study was to (i) evaluate the concurrent validity between a 5 Hz GPS and timing gates for measuring mean speed over 30 m and (ii) examine whether regression analysis could yield an accurate model to predict over-ground speed from GPS values. Sixty elite team sport participants (age: 14.2 ± 0.67 years; stature: 171.6 ± 9.8 cm; body mass: 66.1 ± 12.9 kg) performed one maximal sprint over a 30 m distance and were concurrently measured using a 5 Hz GPS device and infra-red timing gates. Analysis of the mean speeds calculated revealed a significant correlation (r = 0.85, P<0.05) between the measures, but a systematic underestimation of 1.96 km·h-1 (P<0.05) by the GPS (20.89 km·h-1) of the values from the timing gates (22.85 km·h-1). Multiple linear regression analysis, incorporating mean and peak GPS speeds as independent variables, yielded an adjusted R2 of 0.84 (SEE = 0.49 km·h-1) and the equation; timing gate speed = 2.869 + [(0.246 × mean GPS speed) + (0.497 × peak GPS speed)]. On this basis, it is suggested that amongst sportsmen such as these, the current GPS prediction model can provide a valid alternative to timing gates in the assessment of sprint performance over 30 m.